2020
DOI: 10.1038/s41430-020-0652-1
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and COVID-19: evidence, current status and unanswered research questions

Abstract: Patients with diabetes who get coronavirus disease 2019 are at risk of a severe disease course and mortality. Several factors especially the impaired immune response, heightened inflammatory response and hypercoagulable state contribute to the increased disease severity. However, there are many contentious issues about which the evidence is rather limited. There are some theoretical concerns about the effects of different anti-hyperglycaemic drugs. Similarly, despite the recognition of angiotensin converting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
151
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(166 citation statements)
references
References 45 publications
1
151
0
13
Order By: Relevance
“…As of July 17, 2020, the World Health Organisation (WHO) has declared more than 13 million people as a positive confirmed COVID-19 case that results in more than 580.000 deaths [ 1 ]. Through descriptive observational studies, it is well established that patients with comorbidities are disproportionately affected by COVID-19 and associated with worse clinical outcomes [ [2] , [3] , [4] , [5] ].…”
Section: Introductionmentioning
confidence: 99%
“…As of July 17, 2020, the World Health Organisation (WHO) has declared more than 13 million people as a positive confirmed COVID-19 case that results in more than 580.000 deaths [ 1 ]. Through descriptive observational studies, it is well established that patients with comorbidities are disproportionately affected by COVID-19 and associated with worse clinical outcomes [ [2] , [3] , [4] , [5] ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that older adults and those with chronic medical conditions like heart and lung disease and/or diabetes mellitus are at the highest risk for complications from SARS-CoV-2 infection. Of importance, a yet unresolved conundrum relies on the recently hypothesized bidirectional relationship between COVID-19 and diabetes mellitus (12,13). This concept is supported by reports in which impaired glycaemic control is associated with increased risk of severe COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…We emphasize that the dietary co-administration of the antioxidant-rich foods along with clinical treatments may ameliorate chronic illnesses mediated by heightened free radicals in the body. It has particularly been observed that people with chronic illnesses are more vulnerable to clinical complications and deaths by novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) infections [3][4][5]. The on-going coronavirus disease (CoVID-19) pandemic has forced people across the globe to rethink their nutritional habits, switching to antioxidant-rich foods to avoid chronic illness with stronger immunity [6,7].…”
Section: Introductionmentioning
confidence: 99%